Association between maternal socio-demographic factors and low birth weight newborn in a rural area of Bihar, India (South East Asia Journal of Public Health, 2015)
Low birth weight (LBW) is an important cause of perinatal, neonatal and post-natal morbidity and mortality. In developing countries, LBW of newborns is mainly due to the poor socio-economic and environmental conditions of the mother. The aim of the study was to identify and quantify the effects of age, religion, socio-economic status and occupation of mothers, in order to examine which factors were primarily responsible for LBW of babies. In this study, all singleton newborn having a weight of